A comment on the paper by R.I. Khrapko 'On the possibility of an experiment on 'nonlocality' of electrodynamics'. (30th April 2015) - Venediktov, V Yu
Abstract This methodological note is dedicated to the analysis of the imaginary experiment proposed in the paper by R.I. Khrapko 'On the possibility of an experiment on 'nonlocality' of electrodynamics' [Quantum Electronics, 42, 1133 (2012)].